You could do the question the way it is written, but it is far easier to bring the negative power up to the numerator.
y= x^2 - 3. The derivative of that is
dy/dx = 2x The three is a constant and is always dropped when a derivative is taken
d(-3)/dx = 0
If you are a purist and want to solve the question the way it is written, you could do it this way.
dy/dx = d(1)/dx x^-2 - d(x^-2)/dx * 1
======================
(x^-2)^2
dy/dx = - (-2 x^ - 3) / x^-4
dy/dx = 2 x^-3 * x^4
dy/dx = 2 x^(-3 + 4)
dy/dx = 2x ^ 1
dy/dx = 2x <<<<< answer
Answer:
C
Step-by-step explanation:
trust
10 divided by 2 is 5, 5 + 8 is 13
thus f(10)= 13
hope this helps
Answer:
y = -1
Step-by-step explanation:
(y+1)/(x-8) = (-1+1)/(-2-8)
(y+1)/(x-8) = 0
y+1 =0
y= -1
Answer:
20:15
Step-by-step explanation:
baiscally add 4:3
4+3=7
then take the total of 35 and divide it by 7 you'd get 5.
4x+3x=35
7x=35
1x=5
4x=5×4=20
3x=5×3=15
4:3 therefore would be 20:15